2020
DOI: 10.1007/s10879-019-09449-0
|View full text |Cite
|
Sign up to set email alerts
|

Mentalization and Psychosis: A Rationale for the Use of Mentalization Theory to Understand and Treat Non-affective Psychotic Disorder

Abstract: Social functioning can be severely impaired in non-affective psychotic disorder (NAPD). Current models of psychosis pathogenesis do not tend to focus on social dysfunction and pharmacological treatment fails to ameliorate it. In this article, we propose that mentalization theory provides a valuable contribution to the understanding and treatment of NAPD. Impaired mentalizing may contribute to both positive and negatives symptoms as well as social dysfunction observed in NAPD. Furthermore, impaired mentalizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 70 publications
0
29
0
1
Order By: Relevance
“…Nevertheless, integrating the mother into the work with the child allows the therapist to gain awareness of the mother's perception of the child and notice unintegrated and unrealistic parts of her representations. This gains further importance as a recent paper highlighted that psychotic people display problems in detecting and representing their own sensory‐affective experiences but may assign too much weight to these experiences as accurate representations of reality (Weijers et al ., 2020). By inviting the mother to reflect and understand these perceptions – and, if necessary, challenge the experience – the therapist can help the mother to explore her own underlying emotions and how these representations may interfere with the ongoing relationship with her child (Redfern, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, integrating the mother into the work with the child allows the therapist to gain awareness of the mother's perception of the child and notice unintegrated and unrealistic parts of her representations. This gains further importance as a recent paper highlighted that psychotic people display problems in detecting and representing their own sensory‐affective experiences but may assign too much weight to these experiences as accurate representations of reality (Weijers et al ., 2020). By inviting the mother to reflect and understand these perceptions – and, if necessary, challenge the experience – the therapist can help the mother to explore her own underlying emotions and how these representations may interfere with the ongoing relationship with her child (Redfern, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Deficits in mentalizing have been tied to a multitude of poor outcomes [ 103 ]. Research has found that deficits in mentalizing are linked to decreased community engagement, reduced vocational functioning, as well as poorer quality of life [ 90 , 104 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a dynamic practice, MBT-p aims to promote mentalizing ability to strengthen the ability to make sense of interpersonal experiences and to better navigate social life by recognizing how various social situations affect thoughts, feelings, and motivations [ 90 ]. Interventions focus on the patient’s experience in the present through the therapist’s continued curiosity about the patient’s thoughts, feelings, and intentions as well as by encouraging the sharing of narratives of social interactions [ 103 ]. Case studies have reported that MBT-p is linked to improvements in social functioning [ 103 ] and the decrease of negative symptoms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…U osób z rozpoznaniem schizofrenii wykazano związek między metapoznaniem a poprawą funkcjonalną, co uzasadnia zastosowanie terapii opartych na tym koncepcie (Davies i Greenwood, 2018). Dotychczas stworzono kilka programów terapeutycznych ukierunkowanych na poprawę metapoznania (Lysaker et al, 2018) lub mentalizacji (Weijers et al, 2020), lecz przeprowadzono niewiele badań wykorzystujących te terapie u pacjentów we wczesnym okresie schizofrenii. Opublikowano opisy przypadków (Leonhardt et al, 2016(Leonhardt et al, , 2018 i pojedyncze badania obejmujące więcej pacjentów.…”
Section: Terapia Indywidualna We Wczesnej Psychozieunclassified